Protection and Education of Street Children in Islam: A Study of Their Life Experiences - Triana, Dinie; Nurmayani, Nurmayani; Putri, Amelia; Daulay, Nurfitri Humayro; Hani, Aulia (Lembaga Riset Mutiara Akbar, 2025)
The phenomenon of street children is one of the complex social issues in Indonesia. Many factors contribute to children living on the streets, such as poverty, family instability, lack of access to education, and exploitation by certain parties. This study aims to analyze the protection and education of street children from an Islamic perspective, as well as the challenges they face in their daily lives. The research employs a qualitative method using interviews and observations of several street children. The findings indicate that these children encounter various obstacles, including social stigma, lack of family attention, and limited access to education and healthcare. From an Islamic perspective, children have the right to receive protection, affection, and proper education. Therefore, collaboration between families, communities, religious institutions, and the government is necessary to provide sustainable solutions for street children.